Creation of Ready to Wear Deluxe with Manipulating Fabric Slashing Inspired by the Golden Sunrise of Bromo - Kusuma, Karina Septia; Nahari, Inty; Kharnolis, Mein; Arifiana, Deny (PT. Riset Press International, 2024)
The creation of this work is based on a type of practice-led research approach carried out through a fashion design practice studio with a focus on